The cool stuff in Premiere Pro : learn advanced editing techniques to dramatically speed up your workflow - Leirpoll, Jarle (Apress, 2017)
Gain in-depth knowledge of Premiere Pro, and learn how the software "thinks." You'll acquire new skills that will help you choose the best workflow for your project, and simplify and accelerate your video editing process. Learn how you can edit a lot faster with smarter workflows that automate several steps in the editing process. You'll also see how custom settings, presets, keyboard shortcuts and templates saves hours of work. By tailoring the software to your needs you save clicks on just about every task. With many traditional jobs now being done by one person, its important to understand audio smoothing, color grading, motion graphics, and advanced editing techniques. You?ll learn these skills and disciplines and see how they'll enhance your project's workflow. All the authors are professional editors and want to know exactly how to cut your film as fast as possible with top quality output. There is invaluable information in